Synthesis of B6 vitamin - Vučijak Nevena Ž.; Petrović Slobodan D.; Bezbradica Dejan I.; Knežević-Jugović Zorica D.; Mijin Dušan Ž. (Hemijska Industrija, 2009)
The importance of vitamin B6 has been known since its discovery in the 1940's. Chemical tests, elestrometric titration determinations, and absorption spectrum studies showed that this vitamin exists in three major chemical forms: pyridoxine (an alcohol), pyridoxal (an aldehyde), and pyridoxamine (a primary amine). Vitamin B6 is needed for more than 100 enzymes involved in protein metabolism, and it is assumed that this vitamin is cofactor of metabolic processes more important than any other substance. A deficiency of vitamin B6 in the human diet leads to severe disorders. Vitamin B6 is necessary for the proper function of the immune and nervous system, and helps the body convert protein to energy. This paper describes the history, properties and applications of vitamin B6, elucidation of chemical structure, and different procedures for synthesis of pyridoxine and pyridoxamine.